Surgery or conservative therapy – topical issue in radical treatment of laryngeal cancer - Wasilewska-Teśluk, Ewa (Contemporary Oncology/Współczesna Onkologia, 2004)
The definitive criteria for various treatment modalities of the larynx cancer (surgery vs. conservative approaches) are not clear and differ widely according to the treatment center and local experience. The aim of this article was to review recent reports related to conservative radical treatment of laryngeal cancer, which may influence daily clinical practice. The treatment outcomes of conservative treatment and surgery for early stages of laryngeal cancer are comparable but radiotherapy gives better functional results. Primary radiotherapy is also preferred because of the lower risk of late morbidity. Endoscopic laser decortication is recommended for superficial lesions. An important prognostic factor for radical treatment with radiotherapy is tumor volume before treatment. Local tumor control after primary radiotherapy decreases as the tumor volume increases. To date the treatment of choice for advanced laryngeal cancer (T3-T4, N2-N3) was total laryngectomy. Since total laryngectomy resulted in substantial functional morbidity alternative forms of treatment have been developed. To facilitate clinical decisions (surgery vs. conservative treatment) prognostic factors were estimated and are discussed in the article. The results of concurrent chemoradiation or accelerated fractionation schedules of radiotherapy are encouraging. Two-year laryngectomy free survival in about 65% of patients is reported. Loco-regional control following salvage surgery varies from 70% to 90% and two-year overall survival is about 70%. Therefore, overall survival rates of conservative treatment are comparable to surgery followed by postoperative radiotherapy. A specific problem is the management of massive nodal metastases. For large nodal metastases better results may be obtained after neck dissection with postoperative radiotherapy in comparison to radiotherapy alone.